White Over Black : American Attitudes toward the Negro, 1550-1812 - Jordan, Winthrop D. (Book collections on Project MUSE., 2012)
Winthrop Jordan sets out in encyclopaedic detail the evolution of white Englishmen's and Anglo-Americans' perceptions of blacks, perceptions of difference used to justify race-based slavery, and liberty and justice for whites only. This second edition reminds us that this text is still the definitive work on the history of race in America in the colonial era. Every book published to this day on slavery and racism builds upon this work; all are judged in comparison to it; none has surpassed it.